Italian Fertility, 1864 to 1951: An Analysis of Regional Trends - Rachel Franklin (European Regional Science Association (ERSA), 2003)
Below replacement level fertility rates in Italy have received much attention, with varying explanations offered for the protracted decline in fertility rates since the early 1970s. For a more complete understanding of Italian fertility, an analysis of historical fertility trends is useful. This paper employs Italian regional fertility data generated by the Princeton European Fertility Project to evaluate regional patterns of Italian fertility from 1864 to 1951. Regional fertility trends, both temporal and spatial, are described and basic regional convergence methods are applied. The results show that the regional fertility variation seen in Italy since World War II was well established in the 19th century and that a lack of convergence of regional fertility rates during the years of the demographic transition in Italy (late 1800s) helped emphasize regional differences. The impacts of experiences such as political unification, industrialization, the completion of the demographic transition, and mass emigration are cited as important clues to the change and persistence of regional fertility identities during this time period. This use of a rich historical data set placed in a geographic context not only helps illuminate the past, but also assists in the explanation of patterns of regional fertility seen in today's Italy.
Keywords: 330